The Stability of Hydrogen-Bonded Ion-Pair Complex Unexpectedly Increases with Increasing Solvent Polarity - Manna, Debashree; Lo, Rabindranath; Vacek, Jaroslav; Miriyala, Vijay Madhav; Bouř, Petr; Wu, Tao; Osifová, Zuzana; Nachtigallová, Dana; Dračinský, Martin; Hobza, Pavel (Angewandte Chemie (International ed. in English), 2024)
The generally observed decrease of the electrostatic energy in the complex with increasing solvent polarity has led to the assumption that the stability of the complexes with ion-pair hydrogen bonds decreases with increasing solvent polarity. Besides, the smaller solvent-accessible surface area (SASA) of the complex in comparison with the isolated subsystems results in a smaller solvation energy of the latter, leading to a destabilization of the complex in the solvent compared to the gas phase. In our study, which combines Nuclear Magnetic Resonance, Infrared Spectroscopy experiments, quantum chemical calculations, and molecular dynamics (MD) simulations, we question the general validity of this statement. We demonstrate that the binding free energy of the ion-pair hydrogen-bonded complex between 2-fluoropropionic acid and n-butylamine (CH3CHFCOO-…NH3But+) increases with increased solvent polarity. This phenomenon is rationalized by a substantial charge transfer between the subsystems that constitute the ion-pair hydrogen-bonded complex. This unexpected finding introduces a new perspective to our understanding of solvation dynamics, emphasizing the interplay between solvent polarity and molecular stability within hydrogen-bonded systems.
Keywords: Slow-growth dynamics; Hydrogen bonding; NMR; Solvent effect; Micro-solvation